AN ANALYSIS OF THE EFFECT OF SERVICE QUALITY ON SATISFACTION AND LOYALTY WITH ISLAMIC ECONOMIC APPROACH (STUDY ON BMT MEMBERS IN PUSKOPSYAH JAMBI) - LUCKY ENGGRANI FITRI; RIDHWAN RIDHWAN; OKHI FAJAR HARDIANSYAH (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
This study aimed to determine the effect of service quality on satisfaction and loyalty of Baitul Maal Wa Tamwil (BMT) members who become members of the Sharia Cooperative Center (PUSKOPSYAH) in Jambi. The development of BMT in Jambi is quite slow compared to other provinces on the SumatraIsland; so this research was carried out in Jambi City. This research design used quantitative methods with a survey approach. The type of data used was primary data. Primary data were obtained through distributing questionnaires to respondents who members of five BMTs become members of PUSKOPSYAH in Jambi, with a total sample of 140 respondents taken using the purposive sampling method. Quantitative data was processed using the Structural Equation Model (SEM) method with SmartPLS 3 software. From the resultsof this study showed that Service Quality has a significant effect on satisfaction and satisfaction has significant effect on loyalty. Meanwhile, Service Quality variable does not significantly influence the loyalty of BMT members.